Transient tachypnea of the newborn following vaginal delivery in a primigravida: A case report managed with low-flow oxygen via concentrator (Indian Journal of Case Reports, 2026)
Transient tachypnea of the newborn (TTN) is a self-limiting respiratory condition typically associated with delayed clearance of fetal lung fluid. It is more commonly reported after cesarean delivery; however, it may occasionally occur following an uncomplicated vaginal birth. We report a term neonate born to a primigravida who developed tachypnea shortly after birth despite stable oxygen saturation on room air. The infant was managed with low-flow oxygen delivered through a concentrator and supportive care, resulting in gradual clinical improvement. Sepsis and congenital pneumonia were considered and excluded through clinical and laboratory evaluation. Arterial blood gas analysis revealed mild respiratory alkalosis. The neonate recovered completely and remained well on follow-up.